A SnO2/Bi2S3-based photoelectrochemical aptasensor for sensitive detection of tobramycin in milk. (15th May 2021) - Liu, Xiao; Jiang, Yuning; Luo, Jing; Guo, Xiaoyu; Ying, Ye; Wen, Ying; Yang, Haifeng; Wu, Yiping
Highlights: The SnO2 /Bi2 S3 shows significantly improved photoelectrochemical performance. SnO2 /Bi2 S3 with tobramycin -binding aptamer was constructed as aptasensor. The sensor is used to selectively and sensitively determine trace TOB in milk sample. Abstract: Abuse of tobramycin (TOB) causes a series of diseases. Therefore, the development of rapid and sensitive method for analyzing TOB in food products is necessary. In this work, aptamer modified SnO2 /Bi2 S3 -based photoelectrochemical (PEC) sensor was developed for the determination of TOB in milk. Under optimal condition, a wide linear response for TOB from 5 to 50 nmol/L with a limit of detection of 4.28 nmol/L is reached. The possible detection mechanism is that TOB molecules are specifically captured by aptamer, increasing electron transfer resistance and declining the photocurrent. Thanks to the favorably matched energy level of SnO2, and Bi2 S3, the PEC aptasensor exhibits high sensitivity, and with the aid of oxalate, the sensitivity of the sensor is further improved. Importantly, the stability of the PEC aptasensor is also satisfactory due to the calcination of SnO2 /Bi2 S3 at 450 °C.